2021
DOI: 10.1093/cvr/cvab005
|View full text |Cite
|
Sign up to set email alerts
|

TNFα induces endothelial dysfunction in rheumatoid arthritis via LOX-1 and arginase 2: reversal by monoclonal TNFα antibodies

Abstract: Aims Rheumatoid arthritis (RA) is a chronic inflammatory disease affecting joints and blood vessels. Despite low levels of low-density lipoprotein cholesterol (LDL-C), RA patients exhibit endothelial dysfunction and are at increased risk of death from cardiovascular complications, but the molecular mechanism of action is unknown. We aimed in the present study to identify the molecular mechanism of endothelial dysfunction in a mouse model of RA and in patients with RA. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 45 publications
1
9
0
Order By: Relevance
“…Our in vivo and vitro studies confirmed the results and further demonstrated that HCQ could reduce the expression of cytokines, chemokines, and adhesion molecules in uveitic retinas and TNF-a-stimulated inflammation of RVECs. Our findings are in accordance with previous studies on other kinds of endothelial cells, which represent the pathophysiology of different diseases, like atherosclerosis, coronary heart disease, rheumatoid arthritis, and diabetes mellitus (36,37). To conclude, the above results suggest that HCQ may be a promising molecule for treatment of inflammatory vascular diseases owing to its immunomodulatory effects.…”
Section: Discussionsupporting
confidence: 93%
“…Our in vivo and vitro studies confirmed the results and further demonstrated that HCQ could reduce the expression of cytokines, chemokines, and adhesion molecules in uveitic retinas and TNF-a-stimulated inflammation of RVECs. Our findings are in accordance with previous studies on other kinds of endothelial cells, which represent the pathophysiology of different diseases, like atherosclerosis, coronary heart disease, rheumatoid arthritis, and diabetes mellitus (36,37). To conclude, the above results suggest that HCQ may be a promising molecule for treatment of inflammatory vascular diseases owing to its immunomodulatory effects.…”
Section: Discussionsupporting
confidence: 93%
“…Etanercept prevented TNF-induced endothelial cell apoptosis by enhancing the process of autophagy [209]. Moreover, infliximab reversed TNF-α induced endothelial dysfunction as well as the increase in oxLDL, LOX-1, and Arg2 [210]. We have also shown that adalimumab could improve endothelial function and inflammation in patients with psoriasis [211].…”
Section: Tnf-α Inhibitionmentioning
confidence: 66%
“…As a possible abnormal index of anemia in elderly patients with RA, PLR and hs-CRP have no significant correlation with the increase of immunoglobulin, while hs-CRP, as an important indicator of inflammatory response in the early stage of RA, and LDL-C and TC as important monitoring indexes of abnormal lipid metabolism, can better reflect the possibility of atherosclerosis [29,30]. Therefore, anemia in elderly patients with RA is closely related to lipid metabolism and inflammatory reaction [31][32][33]. In clinical treatment one should pay close attention to lipid metabolism and inflammation in RA patients.…”
Section: Discussionmentioning
confidence: 99%